(untitled) (Journal of Economic Research & Business Administration, 2024)
The article outlines the causes why the tax has undergone many changes in economic content and meaning from ancient historical development to the current day. It is determined that taxes arose together with the formation of the state and are the main source of prosperity and development of the state, as well as in modern conditions, when the change and prosperity of the state structure, whatever it may be, are formed together with the reorganization, updating of its tax system. Therefore, the state, through the taxation system, carries out activities for the approval, introduction and collection of taxes. In addition, the State meets the social and economic needs of the State on the basis of the taxation process. The goal of the article is to determine the results of the analysis of the system of development and implementation of taxes and other mandatory payments to the budget in the Republic of Kazakhstan and ways to further develop it. In accordance with these goals, the indicators of budget revenues of the Republic of Kazakhstan, including tax and non-tax payments, were analyzed. An assessment of the dynamics of growth or decline in tax revenues is given and its consequences are determined. A SWOT analysis was carried out covering the strengths and weaknesses, opportunities and risks of the modern tax system of the Republic of Kazakhstan. Improving the efficiency of the local tax mechanism in Kazakhstan is claimed necessary for the economic improvement of the country. In this regard, measures to simplify the newly adopted Tax Code, work on digitalization of tax administration, directions for strengthening tax control, programs to increase the level of education of taxpayers, proposals to increase transparency and improve coordination of types of taxes were considered. Key words: tax, budget, finance, income, expenses, taxation, tax revenues, non-tax revenues, tax system.